A rare complication of otitis media: Gradenigo's syndrome successfully managed on outpatient antimicrobial therapy. (January 2020) - Bowman, Conor; Nakhla, Nada; Amedu, Victoria; Patel, Parag; O'Connor, Ciara; Houston, Angela; Breathnach, Aodhan
Abstract: We report a case of Gradenigo's syndrome successfully managed on an outpatient parenteral antibiotic service. This condition is classically described as a triad of otorrhoea, facial pain in the distribution of the trigeminal nerve and ipsilateral abducens nerve palsy, in the context of otitis media. Due to its rarity and variability in its presentation, it can be difficult to diagnose. A detailed history, examination and neuro-radiology imaging are essential in making the correct diagnosis and multidisciplinary management is imperative. Highlights: The classic triad of GS (otorrhoea, abducens nerve palsy, facial pain) is not always present. Untreated, it can be fatal. Early recognition is vital. Infection can mimic a neoplasm, clinically and radiologically. If there are uncertainties about a diagnosis, samples must be sent to microbiology GS is most effectively managed by an MDT approach This case demonstrates the first known successful treatment of GS facilitated by an OPAT team MRI appearances may lag behind the clinical picture; this should be taken into account when planning radiological follow-up